Implementation of Child Led-Advocacy in Limbangansari Village, Cianjur Regency, West Java, Indonesia - Kuswanda, Dede; Ariska, Dela Vinka; Nurfauziah, Nisa Almalia; Susilawati; Kartika, Tuti (Global Writing Academica Researching and Publishing, 2024)
Basically, children's needs are different from those of adults. It is important for children to voice and advocate for their needs. Children who are able to voice their opinions to fulfill their rights and needs can be referred to as a form of advocacy. Therefore, it is important that advocacy is carried out by children. This study aims to obtain an overview of the Implementation of Advocacy Led by Children in Limbangan Sari Village, Cianjur District, Cianjur Regency. This research uses a descriptive method with a qualitative approach. Primary data sources in this study are children who are informants in this study. Secondary data sources come from books, articles, and research related to child-led advocacy. The data collection techniques used were Focus Discussion Group (FGD), interview, observation, and documentation study. Data validity checking is done through credibility test, transferability test, reliability test, and objectivity test. Data analysis techniques used are data reduction, data presentation, and conclusion drawing. The results of this study are that there are four stages of advocacy led by children, namely identification of problem issues, discussion of problem solving issues, solutions to problem solving issues, and delivery of advocacy. The problem issues of children in Limbangansari Village are the lack of involvement of children in community activities and village organizations; there is no reading corner for children; and the lack of activities that can improve the skills of children in Limbangansari Village. Then, the solutions that have been prepared are delivered by the children directly to the stakeholders of Limbangansari Village.